A qualitative study of the intervention dilemmas and parenting growth experiences for parents of children with autism - DAI Yushen, ZHANG Lifeng, FENG Yongshen, LIU Shaofei, JI Yan, CHEN Miaoying (Xin yixue)
Objective To explore the intervention dilemma of autistic children and their parents’ upbringing and growth experience， aiming to provide evidence for family support measures. Methods Through a descriptive phenomenological study， semi-structured interviews were conducted with 20 parents of children with autism from January to April 2023 at Child Development and Behavior Center of the Third Affiliated Hospital of Sun Yat-sen University. And data were analyzed using Colaizzi’s 7-step method. Results The intervention dilemmas of children with autism were distilled into two themes： lack of knowledge and resources， and intra-family conflict and disagreement. The parenting and growth experiences of parents were distilled into three themes： inclusive and tenacious mentality， multi-dimensional improvement of ability， and family members’ reconstruction of self and life value. Conclusions Parents of children with autism face intervention dilemmas while having positive caring growth experiences. Supporting children with autism and helping parents positively cope with challenges is crucial.